The Concept of wicked problems : improving the understanding of managing problem wickedness in health and social care - Raisio, Harri; Puustinen, Alisa; Vartiainen, Pirkko (Routledge, Taylor & Francis Group, 2018)
This chapter aims to increase the understanding of the sources of problem wickedness and explores the implications for leaders in health and social care. It considers the conceptual criticism and provides examples of wicked problems found in the health and social care sector. The chapter analyzes the conceptual expansions of wicked problems, such as the super wicked problem, wicked ethics, and the wicked game, and assesses their relevance from the health and social care perspective. It describes the theoretical foundations of the concept of wicked problems by affiliating wicked problems to the complexity science framework. Wicked problems are by nature so multidimensional, interrelated and ambiguous that understanding them is a considerable challenge. The concept of wicked problems has been used to describe and explain various societal and organizational issues. Most often these have been issues related to environmental resource management, security and defense, and health and health care.
Keywords: fi=Sosiaali- ja terveyshallintotiede|en=Social and Health Management|